2012
DOI: 10.3390/toxins4020068
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Penicillium nordicum Growth and Ochratoxin A Production by Native Yeasts of Dry Cured Ham

Abstract: Twelve yeast strains isolated from the surface of Italian typical dry-cured hams, belonging to D. hansenii, D. maramus, C. famata, C. zeylanoides and H. burtonii species, and previously selected for their ability to grow in dry-cured ham-like substrates, were screened for antagonistic activity against a toxigenic strain of P. nordicum and inhibition of ochratoxin A (OTA) biosynthesis. On average, yeast inhibitory activity was lowered by increasing fungal inoculum and enhanced by NaCl presence. In the assay con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 42 publications
(72 reference statements)
8
63
0
Order By: Relevance
“…The inhibition was maintained until the end of ripening (8 months). These data confirm the results obtained in a screen for antagonistic activity against a toxigenic strain of P. nordicum and inhibition of OTA biosynthesis conducted by Virgili et al (2011). According to our data and the data of the above authors, it was suggested that bioprotective cultures might be used to inhibit the growth of OTA producing moulds during preripening and ripening of dry cured hams.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The inhibition was maintained until the end of ripening (8 months). These data confirm the results obtained in a screen for antagonistic activity against a toxigenic strain of P. nordicum and inhibition of OTA biosynthesis conducted by Virgili et al (2011). According to our data and the data of the above authors, it was suggested that bioprotective cultures might be used to inhibit the growth of OTA producing moulds during preripening and ripening of dry cured hams.…”
Section: Discussionsupporting
confidence: 94%
“…They were used as biocontrol agents in cereals (Druvefors & Schnurer, 2005), fruits (Guinebretiere, Nguyen-The, Morrison, Recich, & Nicot, 2000) and in coffee (Masoud & Kaltoft, 2006). The biological control of OTA producing moulds by microbial antagonists to improve food safety without affecting the sensory quality and properties of dry cured ham was investigated (Virgili et al, 2011). In particular, the growth of native yeasts such as Debaryomyces, Candida and less frequently Cryptococcus, Rhodosporidium and Rhodotorula, "in vivo" and "in vitro" seems to inhibit the growth of moulds (Sànchez-Molinero & Arnau, 2006;Virgili et al, 2011;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations